PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT KIRANA PERMATA - Pambudi Pambudi; Andi Amri (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to examine whether or not there is an influence on work motivation and work discipline factors on employee performance at PT. Kirana Permata. Employee performance is now an important indicator to support the company's success, both for operational achievement purposes and to achieve competitive advantage and maintain existence. The company always tries to provide policies and rules to encourage employees to achieve the performance desired by the company. so the focus of this research is the importance of managing human resources by considering work motivation and work discipline factors to improve employee performance. The research method applied in this work is descriptive quantitative. Data collection techniques were obtained through the observation process and distributing questionnaires to 50 PT employees. Kirana Permata in the production section of Division A. The sampling technique was carried out using non-probability sampling, namely saturated sampling, this was done by taking all employees in Division A as research samples. The research results indicate that the two aspects raised, namely motivation and work discipline, are able to contribute or have a positive influence on employee performance. The conclusion of the results obtained is that it was found that there is an influence of work motivation factors and work discipline which can have an influence on the performance of employees who work at PT. Kirana Permata with a sig value obtained*, namely 0.000 (0.000 < 0.05) and the coefficient of determination or what can be called r2 square has an achievement of 0.445, meaning that work motivation factors along with work discipline can have an influence on employee performance by 44.5%. Meanwhile, the remaining value of 55.5% is influenced by other variables not included in the discussion of the topic of this scientific work.